The effect of yoga practice on lipid profiles in patients with chronic heart failure - Babkina , T.M.; Smyrnova, G.S.; Mykhailenko, L.A.; Kozarenko, T.M.; Globa, M.V.; Kundina, V.V. (Medicni Perspektivi, 2022)
The aim of the present study was to assess the efficiency of yoga practice in addition to the standard medical therapy in patients with chronic heart failure (HF) and dyslipidemia. One hundred and two patients with chronic HF and dyslipidemia were divided into the control group (CG) – 54 patients and the yoga group (YG) – 48 patients. The CG was prescribed standard therapy for chronic HF (angiotensin converting enzyme inhibitors, β-blockers, aldosterone antagonists, digoxin, loop diuretics, statins, antiplatelet agents) and dyslipidemia. The YG additionally followed lifestyle modification in the form of 1 h daily practice of yoga for a period of 3 months. All patients completed the questionnaire reporting on their age, gender, medical history and treatment. The fasting blood samples were analyzed for total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol, C-reactive protein, interleukin-8 and tumor necrosis factor -α on admission to the department and after 3 months of treatment. The pre-specified duration of the enrollment period was two years and during that time we interviewed 168 patients. Forty-two did not meet the inclusion criteria for the study, 24 patients refused to participate. A total of 102 patients were enrolled, of them, 54 were included into the control group and 48 into the yoga group. At baseline, there were no significant (p>0.05) differences between the groups in clinical characteristics of the patients. On admission to hospital the patients of both groups received standard therapy in comparable doses. By the end of the study, a significant (p<0.05) reduction in TC, TG and LDL-C levels was observed in both groups with a tendency to more considerable changes in YG. Correlation analysis revealed the positive correlation relationship between TC, LDL-C levels and cytokines. The present study has shown that the practice of yoga in addition to the standard therapy in patients with HF and dyslipidemia could be associated with lipid profile improvements.